2014
DOI: 10.1136/jnnp-2014-308764
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase inhibitors for Parkinson's disease: a systematic review and meta-analysis

Abstract: ChIs are effective in the treatment of cognitive impairment in patients with PD, but do not affect risk of falls. The choice of treatment has to be balanced considering the increased tremor and adverse drug reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…Some drug trials have indicated that their use could improve cognition among participants with Parkinson's disease dementia and dementia with Lewy bodies [29]. However, improved cognition in PD through the use of cholinesterase inhibitors can be accompanied by the increased tremor and adverse drug reactions [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Some drug trials have indicated that their use could improve cognition among participants with Parkinson's disease dementia and dementia with Lewy bodies [29]. However, improved cognition in PD through the use of cholinesterase inhibitors can be accompanied by the increased tremor and adverse drug reactions [30]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis suggested that AChE inhibitors are effective in the treatment of cognitive impairment in patients with PD. 120 The systematic search yielded three studies involving donepezil and one involving rivastigmine. Results showed that these drugs significantly slowed MMSE decline (MD=−1.123, 95% confidence interval (CI)=−1.638 to −0.608; P =0.001; I 2 =44.6%), and ADAS-cog (SMD=−0.266, 95% CI −0.399 to −0.133; P <0.0001; I 2 =0%).…”
Section: Cholinergic Disturbances In Pdmentioning
confidence: 99%
“…Cholinesterase inhibitors such as rivastigmine and donepezil can have a positive effect on cognitive function in PD, but may have a deleterious effect on motor function, particularly tremor. 18 Hallucinations can also respond to cholinesterase inhibitors. Quetiapine and clozapine are sometimes used to treat psychosis in PD; however, there is a lack of good evidence from controlled trials to support the use of quetiapine, and while there is better evidence to support the use of clozapine, physicians are often reluctant to use it as it is associated with haematological adverse events.…”
Section: Managing Cognitive and Psychiatric Aspectsmentioning
confidence: 99%